Geology of eastern Dronning Maud Land (Lützow-Holm Complex) and Enderby Land (Napier Complex and Rayner Complex), and geological field project objectives in JARE 65 (2023-2024) - Hokada, Tomokazu; Adachi, Tatsuro; Mori, Yuki; Lakshmanan, Sreehari (2023)
The 14th Symposium on Polar Science/Ordinary sessions [OG] Polar geosciences, Wed. 15 Nov. / 3F Multipurpose Conference room, National Institute of Polar Research conference object